A single amino acid variation of NV protein of viral hemorrhagic septicemia virus increases protein stability and decreases immune gene expression. Issue 116 (September 2021) - Seong, Mi So; Jang, Eun Ah; Kim, Julan; Kim, Woo-Jin; Cheong, JaeHun
Abstract: Viral hemorrhagic septicemia virus (VHSV) causes severe mortality among more than 90 fish species. The 11 kb viral genome encodes six proteins including nonvirion protein (NV). In previous study, we reported that NV gene variations of VHSV decrease cellular energy metabolism. Among several NV mutant proteins, NV-S56L showed the highest cellular energy deprivation. Based on this finding, we further examined a molecular mechanism of one amino acid (S56L) change on differential cellular dysregulation. In the fish cells, the NV-S56L protein showed an increased level of cellular expression than normal and other mutant NV proteins without change of mRNA expression. Using cycloheximide treatment for exclude de novo NV protein expression, NV-S56L had an extensive half-life of intracellular protein. The proteasome inhibitor, MG-132, treatment recovered the all NV protein levels. The ubiquitination of NV was increased in the treatment of MG132 via inhibition of the ubiquitin/proteasome system process. Finally, increased protein stability of NV-S56L led to downregulation of NF-κB response immune gene expression. These results indicate that the prolonged protein stabilization of NV protein variant (NV–S56L) increases its pathological duration and might eventually lead to high virulence activity in the host fish cell. Highlights: Amino acid variations of VHSV NV protein determine protein stabilization. VHSV NV protein stabilization is regulated by ubiquitination and proteasomedependent protein degradation. VHSV NV protein variants decreases immune-related gene transactivation in fish cells.